ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KREDIT BERMASALAH PADA LEMBAGA KEUANGAN MIKRO (LKM) USAHA EKONOMI DESA SIMPAN PINJAM (UED-SP) DI KECAMATAN BANDAR SEI KIJANG KABUPATEN PELALAWAN - Ulfa, Zulia; Nur, Azlina; Julita, Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to obtain empirical evidence about the effect of character, capacity,capital, collateral, condition, loan term at UED-SP in Bandar Sei Kijang Sub-district inPelalawan District. The sample in this research totalled 61 Respondents. Method ofdetermination of the sample using the census method technique of data analysis in thisstudy using multiple linear regression, t-Test and test the assumptions of normality testsinclude classic, multikolonearitas, heteroskedastisitas and autocorrelation datamanagement using program SPSS version 21.0 softwere. From the test results indicatesthat character, capacity, collateral, condition of economy and loan term effect on nonperforming loan (Y)Keywords : Character, Capacity, Collateral, Condition Of Economy, Loan Term, NonPerforming Loan.